STRATEGI PENGEMBANGAN BRANDING DAN IDENTITAS VISUAL UNTUK MEMPROMOSIKAN PRODUK PADA DONAT BAHAGIA GALAXY - Zain, Muhammad Ja'farullah; Sungkono, Sungkono (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to develop branding and visual identity strategies to promote Donat Bahagia Galaxy products. Using a qualitative approach, the research identifies key elements that contribute to effective branding and visual identity design. Through in-depth interviews and visual analysis, the study finds that integrating a strong branding concept with attractive visual identity can enhance the product's appeal to consumers. Essential elements such as the development of a memorable logo, consistent and appealing color schemes, and innovative packaging have been shown to create significant differentiation and increase consumer loyalty. Furthermore, the research highlights the importance of aligning visual elements with brand messaging to create a cohesive and convincing impression in the consumer's mind. The results of this study provide practical guidelines for donut entrepreneurs in optimizing their branding and visual identity strategies to achieve better marketing success.